2021
DOI: 10.5565/rev/clil.68
|View full text |Cite
|
Sign up to set email alerts
|

recerca en aprenentatge de llengües i les percepcions sobre les pràctiques didàctiques a l’aula: el cas de l’ensenyament dels passats en català com a llengua addicional

Abstract: Aquest article té un doble objectiu. D’una banda, fa un repàs a la relació complexa que hi ha hagut entre la recerca en l’ensenyament-aprenentatge de llengües addicionals a persones adultes i les pràctiques a l’aula. Es presenten les diferent posicions que hi ha hagut al voltant del debat i les tendències actuals. D’altra banda, s’il·lustra la relació entre teoria i pràctica a partir d’un estudi sobre les percepcions del professorat de català com a llengua addicional pel que fa a la influència de la recerca en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
3
0
2
Order By: Relevance
“…The finding regarding connection of teaching and research were: 39% of teachers tended to attend conferences and do research in Spanish teaching (33.1% said they did not); research was increasingly important in their teaching profile; and the main constraints for not doing more research were lack of training, lack of professional recognition, and lack of support from their institutions. Comajoan-Colomé (2021) found the relationship between SLA research findings and the declared practices of L2 Catalan teachers. The survey results found that half of the participants declared that their practices had been influenced by research results.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The finding regarding connection of teaching and research were: 39% of teachers tended to attend conferences and do research in Spanish teaching (33.1% said they did not); research was increasingly important in their teaching profile; and the main constraints for not doing more research were lack of training, lack of professional recognition, and lack of support from their institutions. Comajoan-Colomé (2021) found the relationship between SLA research findings and the declared practices of L2 Catalan teachers. The survey results found that half of the participants declared that their practices had been influenced by research results.…”
Section: Introductionmentioning
confidence: 88%
“…It can be considered as a complicated affiliation as far as its practical application is concerned. A number of researchers are supposed to believe that an underlying principle to carry out SLA research is to encourage second language teaching scope (Pica, 2005; Previous studies that investigated the relationship between SLA research and LT can be broadly divided into essaystyle publications, which explore and problematize the relationship between research and practice, and empirical studies, which design specific data-based studies that address the connection between SLA research and LT (Comajoan-Colomé, 2021). EFL teachers in Chile showed their utmost interest in L2 research and found it relevant and very useful as they were mostly positive but found some difficulties in applying research such as lack of time and no financial support in order to access the research (Sato & Loewen, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As such, we consider SLT professionals' research engagement within the framework of the SLT research culture understood globally. This information is important because being part of the SLT research culture, that is, engaging with and in research, has a direct impact on various aspects of SLT professionals' careers such as training, teaching experiences, beliefs and the pedagogical choices they make in the classroom (Borg 2007(Borg , 2009(Borg , 2010(Borg , 2015Comajoan-Colomé 2021).…”
Section: Respondentsmentioning
confidence: 99%
“…Au cours des dernières années, on constate un intérêt croissant pour les études portant spécifiquement sur les pratiques en langues secondes (Comajoan-Colomé, 2021;DeKeyser et Prieto Botana, 2019;Sato et Loewen, 2019), ce qui a mené à une distinction explicite au sein des chercheurs quant à ceux qui s'intéressent à l'acquisition en langue seconde et à ceux qui s'intéressant à l'acquisition en contexte formel (instructed second language acquisition ou ISLA), celle-ci permettant d'explorer comment la manipulation des mécanismes sous-jacents à l'apprentissage et les conditions d'enseignement peuvent faciliter l'acquisition d'une langue (Leow, 2019;Loewen, 2020;Manchón et Leow, 2020). Cette distinction dans la recherche met en lumière l'importance grandissante des liens entre la recherche et la salle de classe afin de mieux soutenir l'apprentissage.…”
Section: Liens Entre Recherche Et Pratiqueunclassified
“…En effet, si l'on prend par exemple le cas de l'apprentissage d'une langue modime comme le catalan, souvent appris comme langue tierce ou additionnelle (L3/Ln) à l'international, Comajoan-Colomé (2021) explique que la plupart des travaux considérant des échanges entre recherche et pratique sont très spécifiques et que ces études se penchent généralement sur des contextes d'apprentissage précis comme celui de l'enseignement obligatoire au secteur des jeunes (maternelle, primaire et secondaire) et peu sur les autres contextes d'apprentissage. Quant aux quelques travaux portant spécifiquement sur la formation des enseignants de catalan comme langue additionnelle (LA) chez les adultes, l'exploration du lien entre la recherche et la pratique a été centrée essentiellement sur les approches méthodologiques pour le design de cours (Bori, 2020;Comajoan-Colomé, 2021;Lacueva, 2017) et moins sur les aspects liés à d'autres enjeux comme le plurilinguisme ou les défis langagiers des apprenants plurilingues dans la formation des enseignants.…”
Section: Liens Entre Recherche Et Pratiqueunclassified